Food security in Brazil - Nordström, Pia (2007)
The analysis of the experiences of Brazil's rural poor over the period of trade liberalisation reveals a complex picture. The impacts of trade liberalisation on the poor seem not to come only from the reduced tariff barriers, but rather from other policies that have accompanied trade liberalisation. In the liberalisation process there may be some groups of individuals that are likely to be disadvantaged, and additional complementary policies will sometimes be needed to enhance the impact from trade, including on poverty. Trade policy will have implications for food security through the link with incomes and expenditures. Any change in the trade regime will have a direct effect on both rural and urban incomes, and employment, and through these on income distribution. The situation of food insecurity and poverty affects about 44 million people in Brazil. The purpose of this study is to examine how the food security situation for the poor households will be affected by a recent proposal of tariff reductions for market access in the WTO negotiations of the Doha round. The study will also consider how the food security situation for the poor households respond to the Zero Hunger Program, which is a social assistance program and includes a combination of structural policies to tackle the underlying causes of poverty. The modelling approach used in the study is a disaggregated Brazilian social accounting matrix. Several household types are taken into consideration so that welfare implications on different income groups of different policy scenarios can be analysed. The analyses include three different scenarios, and the result of the simulations implies that the poor households will benefit and improve their possibilities for a better food security situation. The member states of the United Nations adopted in 2000 the Millennium Declaration as a renewed commitment to human development. The declaration includes eight Development Goals, each with quantified targets to be reach by each member states in 2015. Brazil's Zero Hunger Program is one step towards these Millennium Development Goals.